Resposta agroeconômica da produção de rúcula adubada com húmus de minhoca sucedida pelo cultivo de rabanete - Freitas, Bruna Vieira de (Universidade Federal Rural do Semi-Árido, 2017)
Organic agriculture aims to promote the conservation of the environment in the absence of chemical fertilizers and/or agrochemicals. Among the fertilizers used in organic agriculture there is the vermicomposting, rich in organic matter, which replaces the physical and biological structure of the soil that neutralizes the pH, besides increasing the resistance of plants against pests and diseases. The objective of this paper was to evaluate the production of arugula in function of sources and amounts of humus, earthworm and, subsequently, the production of radish in succession to the cultivation of arugula. Two experiments were conducted at the Experimental Farm Rafael Fernandes, belonging to the Universidade Federal Rural do Semi-Árido (UFERSA), located in the district of Lagoinha. The experimental design was a randomized complete block design with four replications, with treatments arranged in a 2 x 5 factorial scheme. The first factor was composed of two sources of humus (bovine and goat manure) and the second factor of five humus quantities (50, 100, 150, 200 and 250% of N) incorporated in the soil. The cultivars of arugula used was the “Cultivada” and as for the radish was the “Crimson Gigante”. The characteristics evaluated in the arugula were: plant height, number of leaves per plant and productivity of green and dry mass of the shoot. As for the radish were: plant height, stem diameter, number of leaves per plant, total, commercial and root rots productivity, fresh and dry mass of the shoot and dry mass of roots. The economic indicators were also evaluated: gross income, net income, rate of return and profitability index. There were no significant interaction between the sources and amounts of humus studied for any of the characteristics evaluated in the arugula and radish. The highest agro-economic efficiency of arugula and radish was obtained for 250% of N. As pertaining to the agro-economy, both of the sources of earthworm humus can be used. Earthworm humus is economically viable for the production of organic vegetables
Agro-economics answer of arugula production fertilized with worm humus succeeded by radish cultivation
Keywords: Eruca sativa; Crimson Gigante; Vermicomposto; Agricultura Orgânica; Hortaliças; Eruca sativa; Crimson gigante; Vermicomposting; Organic agriculture; Vegetables; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA